PENGARUH PEMBERIAN MANURE AYAM PETELUR TERFERMENTASI DALAM PAKAN YANG DITAMBAH ORGANIC DEODORANT TERHADAP PERFORMA ITIK JANTAN UMUR 7-12 MINGGU - Djuriono (Djuriono) (Buletin Peternakan, 2015)
The research was conducted to analyze the effect of organic deodorant supplemented fermented laying hens manure feeding on the performance of 7-12 weeks male ducks. One hundred 7 weeks old male ducks were used to study the effetct MODF supplementation on performance of male ducks. The ducks were divided into five groups with four replications consisting of five birds each. The treatment were PO = commercial feed without MODF supplementation (control), P15= commercial feed + 15% MODF, P30= commercial feed + 30% MODF, P45= commercial feed + 45% MODF, P60= commercial feed + 60% MODF. Data were analyzed with One-Way Classification of Completely Randomized Design and followed by Duncan’s New Multiple Range Test (DMRT) for significant results. Results showed that supplementation of fermented MOD gave negative effect (P<0.05) on male ducks performance. The highest consumption was in P0 (5203.50 g), followed by P45% (5130.00 g), P30% (5002.75 g), P15% (4967.75 g), P0% (4856.75 g). The highest weight gain showed in P0 (649.80 g), followed by P15 (622.10 g), P30 (579.45 g), P45 (497.50 g), P60 (409.60 g). The higest feed convertion was in P60 (12.71), followed by P45 (10.31), P30 (8.64), P15 (7.99), P0 (7.48). It could be concluded that it is useless to supplement commercial diet of with MODF even though supplementation of 30% income over feed cost (IOFC) showed better IOFC of 7-12 weeks male ducks.(Key words: Fermentated organic deodorant, Laying hens manure, Males ducks, Performance)